Vignettes in Patient Safety Volume 4 - Stawicki, Stanislaw P.; Firstenberg, Michael S. (IntechOpen, 2019)
Medical errors contribute significantly to morbidity and mortality across our healthcare institutions. Due to the increasing complexity of the modern medical practice, a perfect storm of regulatory, market, social, and technical factors, and other competing priorities, created an environment that is primed for patient safety lapses. The spectrum of contributing variables - ranging from minor errors that subsequently escalate, poor communication, and protocol/process non-compliance (just to name a few) - is extensive and solutions are only recently being described. As such, there is a growing body of research and experiences that can help provide an organized framework - based on best practices and evidence-based medical principles - for healthcare organizations to develop, implement, and embrace. Based on the tremendous interest in the initial three volumes of our Vignettes in Patient Safety series, this fourth volume follows a similar model of outlining a patient safety case based on experiences that many clinicians can relate to, and then discusses various factors that may have contributed to a medical error, complication, and/or poor outcome. Building on a problem-based clinical vignette, each chapter then outlines an evidence-based approach to present any related literature, pertinent evidence, and potential contributing factors and solutions to common patient safety occurrences. By focusing on some of the best practices, structured experiences, and objective approaches to medical error genesis, the authors and editors hopefully can lend some insights into how we can make healthcare encounters for all patients, across all settings, better and safer.